2023
DOI: 10.1038/s41598-023-46013-2
|View full text |Cite
|
Sign up to set email alerts
|

Crystals structures of carbonate phases with Mg in Triassic rocks, mineral formation and transitions

Katarzyna J. Stanienda-Pilecki

Abstract: Detailed data on carbonate minerals different in magnesium content including their crystal structures were presented in this article. The samples were collected from the formations of the Lower Muschelkalk and the Upper Muschelkalk. X-ray diffraction and electron microprobe analysis were used for carbonate phases determination. The following minerals with different Mg content were identified: low-Mg calcite, high-Mg calcite, proto-dolomite, ordered dolomite and de-huntite. The content of Mg in high-Mg calcite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Therefore, this mineral phase was named de-huntite. The reduced magnesium content in de-huntite is probably the effect of the process of advanced-stage diagenesis-dehuntization [46]. This cannot exclude the theory, which assumes that the determined de-huntite phase may represent a huntite-dolomite solid solution or mixture.…”
Section: Mineral Phases and The Trace Elements Of The Triassic Dolomitesmentioning
confidence: 96%
See 3 more Smart Citations
“…Therefore, this mineral phase was named de-huntite. The reduced magnesium content in de-huntite is probably the effect of the process of advanced-stage diagenesis-dehuntization [46]. This cannot exclude the theory, which assumes that the determined de-huntite phase may represent a huntite-dolomite solid solution or mixture.…”
Section: Mineral Phases and The Trace Elements Of The Triassic Dolomitesmentioning
confidence: 96%
“…The results of studies in the sample micro-areas have shown that high-magnesium calcite has a Mg content higher than "pure" (low-Mg) calcite but lower than that of protodolomite [34,36,46]. The protodolomite is characterized by a lower content of magnesium in relation to the stoichiometric value for dolomite but higher than that of high-magnesium calcite [34,36,46]. Ordered dolomite has a content of Mg close to the stoichiometric value.…”
Section: Mineral Phases and The Trace Elements Of The Triassic Dolomitesmentioning
confidence: 99%
See 2 more Smart Citations